Fairness, trade, and inequality - Hartmut Egger; Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2008)
We develop a model of international trade between two symmetric countries that features inter-group inequality between entrepreneurs and workers, and also intra-group inequality within each of those two groups. Individuals in the economy are heterogeneous with respect to their entrepreneurial ability, and firms run by more able entrepreneurs have a higher productivity level and make higher profits. There is rent-sharing at the firm level due to fair wage preferences of workers, and hence firms with higher profits pay higher wages in equilibrium in order to elicit their workers' full effort. We show that in this framework international trade leads to a self-selection of the best firms into export status, and aggregate welfare increases if this selection effect is sufficiently strong. Gains from trade are accompanied by larger inequality along multiple dimensions: Involuntary unemployment and income inequality between entrepreneurs and workers increase, and so does inequality within these two subgroups of individuals, as measured by the respective Gini coefficients
Keywords: F12; F15; F16; 330; Heterogeneous firms; income inequality; fair wages; unemployment; Außenwirtschaftstheorie; Verteilungstheorie; Leistungsorientierte Vergütung; Produktivität; Außenhandelsgewinn; Unfreiwillige Arbeitslosigkeit; Einkommensverteilung; Theorie